«FIRST BROUGHT INTO ORDER»: CÓMO EDMUND BOLTON LEYÓ A TÁCITO. - PINEDA, VICTORIA (Talia Dixit, 2020)
This review examines the edition of Edmund Bolton's commentary on the first six books of Tacitus's Annals by Patricia Osmond and Robert Ulery. The editors' reading and interpretation of Bolton's treatise within the historiographic, political and social context of Jacobean England are also described.